2016
DOI: 10.1111/jeu.12318
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Characterization and Immunity Identification of Microneme 3 of Eimeria acervulina

Abstract: The gene of Eimeria acervulina microneme protein 3 (EaMIC3) was cloned and characterized. According to the conserved sequence, the 3'- and 5'-ends of EaMIC3 were amplified by the rapid amplification of cDNA ends (RACE). The full length cDNA of this gene was obtained by overlapping the sequences of 3'- and 5'-extremities and amplification by reverse transcription PCR. The sequence analysis revealed that the opening reading frame (ORF) of EaMIC3 was 2,607 bp and encoded a protein of 868 amino acids with 93.04 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Jenkins et al [ 66 ] showed the immune-mapped protein 1 could be detected in the sporozoites. Zhang et al [ 31 ] found EaMIC3 on the apical tip of E. acervulina sporozoites. Our findings suggest that EmSAG is expressed in the sporozoite and merozoite stages of E. maxima , and might play an important role in the host invasion mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jenkins et al [ 66 ] showed the immune-mapped protein 1 could be detected in the sporozoites. Zhang et al [ 31 ] found EaMIC3 on the apical tip of E. acervulina sporozoites. Our findings suggest that EmSAG is expressed in the sporozoite and merozoite stages of E. maxima , and might play an important role in the host invasion mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The counts of T cells in the treatment groups were evaluated by flow cytometry analysis as previously described [ 30 , 31 ]. Spleens were extracted from 5 chickens of each group at pre-, first-, and second-vaccination days.…”
Section: Methodsmentioning
confidence: 99%
“…Chapman and Shirley (102) used a modified version of the former protocol and assigned cut-offs for drug sensitivity; >160 = sensitive, partially resistant = 120-160 and <120 = resistant. Some vaccine studies have used ACI as a method to evaluate vaccine efficacy and assigned different cut-off scores for efficacy with some variation between studies; an ACI of <160 is generally considered to be ineffective (103)(104)(105)(106)(107). However, whether this adapted scoring method is overly simplistic to evaluate the efficacy and usefulness of vaccines in the field has yet to be determined.…”
Section: Composite Measures Of Efficacymentioning
confidence: 99%
“…Interference of c-Cbl expression can promote apoptosis by upregulating the expression of Fas and DR4/5 ( 33 , 34 ). Also, c-Cbl can degrade caspase-8 by ubiquitination and then inhibit cell apoptosis in gastric cancer ( 35 ). This result suggests that c-Cbl can inhibit host cell apoptosis via substrate protein ubiquitination.…”
Section: Discussionmentioning
confidence: 99%